Isolation and characterization of a human monoclonal antibody that recognizes epitopes shared by Pseudomonas aeruginosa immunotype 1, 3, 4, and 6 lipopolysaccharides. - Lang, A B (1989)
A hybridoma line secreting a human monoclonal antibody (HMAb) capable of recognizing Fisher immunotype (IT) 1, 3, 4, and 6 lipopolysaccharide (LPS) in vitro was isolated. Peripheral blood lymphocytes (PBL) were obtained from volunteers immunized with an experimental Pseudomonas aeruginosa O polysaccharide-toxin A vaccine. PBL-expressing surface antibodies able to bind to P. aeruginosa LPS were isolated by adsorption onto LPS-coated plastic wells. Such PBL were transformed with Epstein-Barr virus. Lymphoblastoid cell lines secreting anti-P. aeruginosa LPS antibodies were identified by an enzyme-linked immunosorbent assay and fused to the F3B6 heteromyeloma line. A hybridoma line producing a HMAb (2-8AH79) able to bind IT-1, IT-3, IT-4, and IT-6 LPS was identified by an enzyme-linked immunosorbent assay. This HMAb was found to bind to the O-polysaccharide regions of IT-1, IT-3, IT-4, and IT-6 LPS, as determined by immunoblotting. By using an immunofluorescence microscopy assay, the cell surfaces of IT-3 and IT-4 bacteria were strongly stained by HMAb 2-8AH79, whereas those of IT-1 and IT-6 bacteria were weakly stained. This HMAb was found to promote the uptake and killing of IT-3 and IT-4 bacteria, but not IT-1 or IT-6 organisms, by human polymorphonuclear leukocytes. Similarly, the passive transfer of HMAb 2-8AH79 to mice afforded significant protection only against a challenge with IT-3 and IT-4 bacteria.